2018
DOI: 10.1039/c8ra06704j
|View full text |Cite
|
Sign up to set email alerts
|

Purification and structural elucidation of chondroitin sulfate/dermatan sulfate from Atlantic bluefin tuna (Thunnus thynnus) skins and their anticoagulant and ACE inhibitory activities

Abstract: Chondroitin sulfate/dermatan sulfate (CS/DS) was extracted from Atlantic bluefin tuna (Thunnus thynnus) skin (SGAT) and was purified and characterized. SGAT was characterized by acetate cellulose electrophoresis, FTIR spectroscopy, 13 C NMR spectroscopy and SAX-HPLC. According to the results obtained for specific chondroitinases (ABC and AC) and the SAX-HPLC separation of generated unsaturated repeating disaccharides, the polymer was found to contain a disaccharide monosulfated in positions 6 and 4 of GalNAc a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 57 publications
2
6
0
Order By: Relevance
“…The characteristic peaks of S=O were observed at 1223, 1231, 1230, and 1230 cm −1 for standard CSA, CSC, and CS derived from skipjack and yellowfin tuna heads, respectively. The results were in line with previous studies on extracted samples of buffalo tracheal, nasal and joint cartilages [ 61 ]; crocodile hyoid, rib, sternum, and tracheal cartilages; shark fin; ray cartilage; chicken keel cartilage [ 60 ]; cephalopods [ 75 ]; and Atlantic bluefin tuna skins [ 77 ]. The characteristic peaks of C–O–S were observed at 854, 829, 833, and 839 cm −1 for standard CSA, CSC, and CS extracted from skipjack and yellowfin tuna heads, respectively.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…The characteristic peaks of S=O were observed at 1223, 1231, 1230, and 1230 cm −1 for standard CSA, CSC, and CS derived from skipjack and yellowfin tuna heads, respectively. The results were in line with previous studies on extracted samples of buffalo tracheal, nasal and joint cartilages [ 61 ]; crocodile hyoid, rib, sternum, and tracheal cartilages; shark fin; ray cartilage; chicken keel cartilage [ 60 ]; cephalopods [ 75 ]; and Atlantic bluefin tuna skins [ 77 ]. The characteristic peaks of C–O–S were observed at 854, 829, 833, and 839 cm −1 for standard CSA, CSC, and CS extracted from skipjack and yellowfin tuna heads, respectively.…”
Section: Resultssupporting
confidence: 91%
“…The characteristic peaks of C–O–S were observed at 854, 829, 833, and 839 cm −1 for standard CSA, CSC, and CS extracted from skipjack and yellowfin tuna heads, respectively. The results were in line with previous studies on extracted samples of buffalo tracheal, nasal, and joint cartilages [ 61 ]; crocodile hyoid, rib, sternum, and tracheal cartilages; shark fin; ray cartilage; chicken keel cartilage [ 60 ]; cephalopods [ 75 ]; Atlantic bluefin tuna skins [ 77 ]; and Nile tilapia ( Oreochromis niloticus ) bones [ 78 ]. The slight variation in this characteristic peak observed in this study indicated that they were made up of different proportions of CSC and CSA [ 60 , 61 ].…”
Section: Resultssupporting
confidence: 90%
“…Only a few reports have focused on the ACE-inhibitory activity of marine GAGs. The ACE-inhibitory activity of GAGs from tub gurnard skin was slightly lower than what was reported by Karimzadeh [ 22 ] for GAGs extracted from sturgeon cartilage (85.7% ACE inhibition at a concentration of 1 mg/mL), and by Krichen et al [ 23 ] for GAGs from Atlantic Bluefin tuna skin (70.81% at a concentration of 0.8 mg/mL). The ACE-inhibitory activity was also lower than the values reported by Abdelmalek et al [ 24 ] for GAGs released from common squid skin (50% at 0.14 mg/mL).…”
Section: Resultsmentioning
confidence: 55%
“…The total sugar content in CSDB, as determined using the phenol–sulfuric acid method, was 93.10% ± 0.54, which is higher than that reported in CS from smooth-hound cartilage (89.43%), Atlantic bluefin tuna skin (80.12%), 42,43 and chicken cartilage (20.47%). 41 Next, the total uronic acid content in sturgeon CSDB, as determined using the carbazole method, was 71.12% ± 1.03, which is similar to that reported in CS from Atlantic bluefin tuna (69%), smooth hound cartilage (80.7%), 42,43 and chicken cartilage (40.92%). 38…”
Section: Resultsmentioning
confidence: 56%